Masculinization of Banggai Cardinalfish (Pterapogon kauderni) using 17α-Methyltestosterone-enriched Artemia sp. - Muhammad Safir; Desiana Trisnawati Tobigo; Seftina F Mangitung; Madinawati Madinawati; Zainab Zainab (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
Banggai Cardinalfish (Pterapogon kauderni) is one of the endemic fish from the waters of the Banggai Islands, Central Sulawesi Province. One factor challenging the production of P. kauderni larvae is the male fish will nurture the eggs and larvae for 30 days, hindering next spawning cycle. One effort to overcome this problem an increase of male fish number should be performed, for example through sex reversal. This study aimed to determine the effectiveness of the hormone 17α-methyltestosterone (17α-MT) through Artemia sp. to increase male sex percentage P. kauderni. This study used a completely randomized design by testing four treatments namely feeding Artemia sp. which has been soaked with 2.0 mg of the 17α-MT hormone for two- hours given to P. kauderni larvae for 10 days (A); 20 days (B); 30 days (C), and without hormone treatment 17α-MT (control). Each treatment included control was performed in triplicates. The percentage of male sex was 93.33 % at 30 days treatment and was higher (P<0.05) compared to controls (53.3 %). Additionally, the results showed that daily growth rate, biomass gain and survival rate of all treatments were not significantly different (P>0.05) with those of control. In conclusion, Artemia sp. contained 17α-methyltestosterone enhanced male percentage of P. kaurderni. Keywords: growth, male percentage, Artemia sp., survival rate, Pterapogon kauderni